THE ROLE OF THE ENGLISH LANGUAGE TEACHER IN DEVELOPING COMMUNICATIVE COMPETENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the crucial role of the English language teacher in developing students’ communicative competence. It highlights the teacher’s responsibilities in creating an interactive learning environment, employing effective teaching methodologies, and fostering both receptive and productive language skills. The study emphasizes strategies for enhancing speaking, listening, reading, and writing abilities, while also addressing the importance of cultural awareness and learner motivation in language acquisition. The article demonstrates that the teacher’s professional competence, pedagogical approach, and engagement with students significantly influence the development of communicative skills.